HPLC Method Optimization for Simultaneous Determination of Quercetin, Luteolin, Sinensetin, and Stigmasterol in Herbal Medicines - Asih Imulda Hari Purwani; Riesta Primaharinastiti; Mochammad Yuwono (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Quercetin, luteolin, sinensetin and stigmasterol each is the main marker compound in extracts of Sonchus arvensis, Plantago major, Orthosiphon stamineus, and Strobilanthes crispus, respectively. These extracts show nephrolithiasis activity. For quality control of herbal medicines, a high performance liquid chromatography (HPLC) method has been developed in this study using quercetin, luteolin, sinensetin and stigmasterol as phytochemical markers. Objective: to show optimal conditions of analysis and evaluate the stability of quercetin, luteolin, sinensetin and stigmasterol. Methods: The optimal conditions for analysis were carried out by determining the composition of the mobile phase, the flow rate, and the detector's wavelength. Zorbax Eclipse Plus C18 150 x 4.6 mm, 5 Î¼m was used as the column. The stability test was done by analyzing the standard and samples stored at 4oC for 0, 3, 6 and 24 hours. Results: The best separation of the extract was achieved under isocratic conditions using a mixture of water: methanol: phosphoric acid: acetic acid : acetonitrile (50: 30: 0.05: 0.05: 20 v/v/v/ v/v) as mobile phase with detector wavelength of 352 nm, a mobile phase flow rate of 1 mL/min, and a sample injection volume of 10 Î¼L. Conclusion: In this study, the optimal condition for analysis of quercetin, luteolin, sinensetin and stigmasterol. Quercetin, luteolin, sinensetin and stigmasterol were not stable during 6 hours storage, therefore, standard solutions and samples should be made fresh to maintain the stability.